The Essence Of The Concept Of Insult - Toliyeva, Shoira Ilhomovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the legal and social essence of the concept of insult, its forms, consequences, and liability measures established by the legislation of the Republic of Uzbekistan based on a scientific approach. The article also pays special attention to the expansion of insults via the Internet and social networks, their negative impact on society, and measures to prevent them.